Prevention of hepatitis B - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula Jolanta (Journal of Education, Health and Sport, 2017)
Hepatitis B (Hepatitis B) is a hepatitis B virus (HBV) -based liver disease. This virus has an affinity for liver cells, it can cause both acute and chronic viral infections of varying severity. The consequences of chronic HBV infection can be cirrhosis and liver cancer. In Poland in 1989 a preventive program was implemented to reduce HBV infection. Universal vaccinations have been introduced to reduce the prevalence of Type B hepatitis B from 40.3 / 100,000 in 1989 to 7/100 in 2000. In the last 20 years in Poland there has been huge progress in the prevention and suppression of HBV infections. Decrease in the incidence of hepatitis B is mainly the result of the introduction of compulsory vaccination and improving hygiene procedures and improve sanitation aimed at aborting the pathways of the virus. However, still a large part of society is not immune on HBV infection acting potential group of the risk of infection. In addition, in the era of a growing group of followers. movements of the anti vaccine it is necessary to continue to promote knowledge of HBV and the efficacy and safety of vaccination.